2020
DOI: 10.1111/psyp.13657
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral mechanisms of hypnotic hypoesthesia. An ERP investigation on the expectancy stage of perception

Abstract: The present study aims at identifying reliable markers of neural preparatory processes during hypnosis. To this goal, we recorded the electroencephalographic activity of 23 volunteers regardless of their hypnotizability score. Somatosensory evoked potentials (SEPs) were elicited while participants received non-painful electrical stimuli on the left median nerve in the conditions of relaxation and hypnosis with suggestions of reduced sensation. SEPs analysis was focused on the pre-stimulus activity and revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 91 publications
1
4
0
Order By: Relevance
“…It is also noteworthy that recent investigations revealed that hypnotized participants' brain activity may undergo opposite patterns as a result of different hypnotic instructions. For example, the suggestion to ignore the external stimuli in a passive task decreased executive control by the PFC (Perri et al, 2020), whereas this control increased with the suggestion to process the external stimuli in an active task (as in this study; see also Huber et al, 2013;Zahedi et al, 2017Zahedi et al, , 2019.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…It is also noteworthy that recent investigations revealed that hypnotized participants' brain activity may undergo opposite patterns as a result of different hypnotic instructions. For example, the suggestion to ignore the external stimuli in a passive task decreased executive control by the PFC (Perri et al, 2020), whereas this control increased with the suggestion to process the external stimuli in an active task (as in this study; see also Huber et al, 2013;Zahedi et al, 2017Zahedi et al, , 2019.…”
Section: Discussionsupporting
confidence: 59%
“…On the other hand, the two suggestions might produce specific ERP alterations in the early or late stages of poststimulus processing, with the perceptual one affecting occipital activity (the visual P1 and N1) and the semantic one producing effects starting from the frontal N300/N400 component associated with conflict detection ( Liotti et al, 2000 ; Badzakova-Trajkov et al, 2009 ; Szűcs and Soltész, 2010 ; Sahinoglu and Dogan, 2016 ). In addition, in the present study, we test the involvement of the activities associated with the anterior insula (aIns) in light of recent investigations showing the contribution of this region to early prefrontal ERPs in visual tasks ( Perri et al, 2014b , 2015 , 2017 , 2018a , b , 2019a ; Ragazzoni et al, 2019 ). The aIns is particularly relevant for the purpose of the present study in that the activity of this region is commonly associated with sensory awareness and decision-making (for reviews, see Craig, 2002 , 2010 ) and supports the perceptual alterations induced by hypnosis ( Perri et al, 2019b ).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Interestingly, the suggestions for analgesia have been found effective also in healthy mediums undergoing nociceptive stimulation (Fidanza et al, 2017 ) and in chronic pain patients independently from hypnotizability (Elkins et al, 2007 ; Jensen, 2011 ; Jensen and Patterson, 2014 ; Mazzola et al, 2017 ; Facco et al, 2018 ; Sandvik et al, 2020 ). This can be accounted for by expectation of/motivation to analgesia (Milling et al, 2005 ; Krystek and Kumar, 2016 ; Montgomery et al, 2018 ; Perri et al, 2020 ) leading to placebo responses (Benedetti, 2013 ) which can reduce pain and pain-related psychological symptoms in the general population (Liossi et al, 2006 ; Brugnoli, 2016 ; Wortzel and Spiegel, 2017 ; Rousseaux et al, 2020 ). Thus, suggestions may induce non opioid analgesia in highs, opioid placebo responses in lows and, probably, mixed reactions in mediums.…”
Section: Suggestions For Analgesiamentioning
confidence: 99%
“…Our hypothesis was that the reduced excitability of the lDLPFC could enhance the hypnotizability and allow for a more intense response on different kinds of hypnotic suggestions. In fact, changes in the DLPFC activity during hypnosis were associated with altered executive control (for a review see Landry et al 2017 ), and deactivation of the left hemisphere seems to best reflect the reduction of peripheral awareness during neutral hypnosis ( Dienes & Hutton, 2013 ; Perri et al, 2020 b). The contribution of the DLPFC in the hypnotic phenomena was also emphasized by the COLD control theory ( Dienes et al, 2012 ; Dienes & Perner, 2007 ), according to which hypnosis would consist in the inaccurate ‘higher order thoughts’ (HOTs) leading to the subjects being unaware of his/her intentions in motor and cognitive actions.…”
Section: Introductionmentioning
confidence: 99%